Ormeloxifene in acute heavy menstrual bleeding in menopausal transition - Shrestha, Subha; Thapa, Babita; Baniya, Sebina; Pandey, Vivek (Asian Journal of Medical Sciences, 2021)
Background: Ormeloxifene, a selective estrogen receptor modulator, is a safer, cost effective and convenient dosing medical therapy in heavy menstrual bleeding of acute abnormal uterine bleeding. Aims and Objective: The study aimed to find the effectiveness of Ormeloxifene as 1st line therapy for heavy menstrual bleeding in menopausal transition women to prevent unnecessary hysterectomies and improve quality of life. Materials and Methods: This descriptive study was conducted at Lumbini Medical College for a period of one year. Sixty-five cases of acute Abnormal Uterine Bleeding with heavy menstruation during menopausal transition period were provided with Ormeloxifene therapy of 60 milligrams dose two times per week after evaluating pre treatment hemoglobin percentage, Pictorial Blood Loss Assessment Chart (PBAC) score and endometrial thickness. The dose of the drug was reduced to 60 mg weekly after 3rd month if subjective improvement was documented and continued for further 3 months. Results: There was a statistically significant reduction in mean PBAC score, mean endometrial thickness and rise in hemoglobin level. Eighty percentages of women had marked subjective improvement of symptoms, 87.7% women had reduction of blood clots, 15. 8% women had relief from dysmenorrheal pain and 50.8% women had regularization of menstrual pattern after 6 months. Amenorrhea (25.3%) was the most common side effect reported in 6 months therapy. Conclusion: Ormeloxifene is an effective 1st line medical therapy in acute heavy menstrual bleeding in menopausal transition women.